The Effect of Sardines Fish Oil Waste Into The Diets on The Chemical Quality of Laying Hen Egg - Anik Fadlilah; Edy Susanto; Husnul Muthoharoh; Ida Susila; Wahyuni Wahyuni; Edi Sutanto; Ike Mawarni Handayani; M. Dzulfikri Alilmi; M. Muhid Mustofa (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2023)
The Functional eggs could be used as food for stunting sufferers. Functional eggs could be produced by feed modification using sardines fish oil waste (SFOW) into diets.  This research determined the effect of sardines fish oil waste on the diets of UD Sumber Rejeki. The material used chicken eggs produced by 60 laying hens aged 12 months. The method used in this study was laboratory analysis with a completely randomized design consisting of 4 treatments and 3 replications. The treatments were mainly fed by adding 0%, 5%, 10%, and 15% SFOW. Laying hens were given treatment for 1 month and then the eggs produced were tested for chemical quality which included levels of protein, fat, water, carbohydrates, total energy, and cholesterol. The research data were analyzed using analysis of variance and continued by testing the average smallest significant difference (BNT). The sardines fish oil waste into the diets did not affect the protein, fat, moisture, and carbohydrate content of laying hen eggs, and significant effect on energy total and cholesterol content of laying hen egg. The chemical quality of laying hen egg consist of a protein content was 12.18-12.47%, fat content was 7.79-8.89%, moisture content was 76.45-77.58%, carbohydrate content was 0.93-1.44%, ash content eggs was 0.88-0.94%, the energy total was 125.75-134.54 Kcal/100 gram, and egg cholesterol content was 267.04-365.68 mg/100g egg. Based on the results of this research, the best addition of waste sardine fish oil was 5% to production costs efficient to produce functional eggs in UD Sumber Rejeki for stunting sufferers, especially in the Lamongan Regency